Optimizing Blockchain Digital Signature Security in Driving Innovation and Sustainable Infrastructure - Agung Rizky; Nugroho, Rayhan Wahyu; Wahyu Sejati; Mumpuni; Omar Sy (IAIC Bangun Bangsa, 2025)
Indonesia experienced a significant spike in cyberattacks, averaging 158 attacks per second, indicating a high risk for digital systems, especially in the government and business sectors. The large number of attacks has caused financial losses and damaged public trust, indicating that data protection is not optimal. Traditional authentication systems based on centralized servers increase the risk of document leaks and forgery. To address this, this study proposes a Blockchain-based digital signature solution called AlphaSign. This technology strengthens data resilience and document verification reliability with an Agile Scrum approach, enabling iterations that are responsive to user needs. Alpha Sign aims to create a secure Blockchain-based digital signature system, prevent document forgery, and accelerate verification through QR code automation. This system supports the development of sustainable digital infrastructure, in line with the SDGs, especially Goal 9 (Infrastructure Innovation) and Goal 16 (Resilient Institutions). With Blockchain technology, Alpha Sign records each signature in a decentralized manner, reduces the risk of hacking, and enables real-time document verification through QR codes, providing security and transparency for large agencies and the public sector.